2022
DOI: 10.1159/000527146
|View full text |Cite
|
Sign up to set email alerts
|

Computational Theories of Alcohol Use Disorder: Mapping Learning and Choice Mechanisms on Symptoms

Abstract: Alcohol use disorder (AUD) is characterized by a combination of symptoms including excessive craving, loss of control, and progressive neglect of alternative pleasures. A mechanistic understanding of what drives these symptoms is needed to improve diagnostic stratification and to develop new treatment and prevention strategies for AUD. To date, there is no consensus regarding a unifying mechanistic framework that accounts for the different symptoms of AUD. Reinforcement learning (RL) and economic choice theori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 180 publications
0
5
0
Order By: Relevance
“…Given the well-documented comorbidities between ADHD and SUD/AUD, perhaps attributable to their shared core symptoms of impulsivity [ 85 , 86 ], we should consider the potential influence of these impulsive disorders on action–value processing effects [ 87 , 88 ]. E.g., Sebold et al [ 89 ] demonstrated that AUD is associated with alterations in value-based decision-making. Furthermore, in the context of SUD, Groman et al [ 90 ] conducted a review and showed evidence suggesting that value updating following positive outcomes, but not negative outcomes, predicts escalation in SUD.…”
Section: Discussionmentioning
confidence: 99%
“…Given the well-documented comorbidities between ADHD and SUD/AUD, perhaps attributable to their shared core symptoms of impulsivity [ 85 , 86 ], we should consider the potential influence of these impulsive disorders on action–value processing effects [ 87 , 88 ]. E.g., Sebold et al [ 89 ] demonstrated that AUD is associated with alterations in value-based decision-making. Furthermore, in the context of SUD, Groman et al [ 90 ] conducted a review and showed evidence suggesting that value updating following positive outcomes, but not negative outcomes, predicts escalation in SUD.…”
Section: Discussionmentioning
confidence: 99%
“…We believe all of these are important factors in developing a more thorough model of alcohol use disorder, and we aim to include them in the future. Other researchers have included some of these features in models of alcohol use disorder [38][39][40], but these other models were not structured as neural networks making it difficult to understand how modifications to the models could translate to potential treatments. In this study, by ignoring these complicating factors, we were able to improve generalizability and simplicity, which we felt was paramount to our research program at this stage.…”
Section: Limitations and Advantages Of The Modelmentioning
confidence: 99%
“…Drinking may thus escalate when decision-making processes in dopamine-innervated frontostriatal circuits are characterized by low executive control or high alcohol valuation (Camchong et al, 2014;Goschke, 2014;Sebold et al, 2022;Zucker, 2015). Chronic alcohol use reinforces this imbalance, thereby facilitating value-based impulsive and stimulus-driven habitual decisions that characterize dependent drinking (Camchong et al, 2014;Goschke, 2014;Sebold et al, 2022;Zucker, 2015).…”
Section: Neurobiology Of Decision-making and Related Drinkingmentioning
confidence: 99%
“…Another study in healthy adults targeted frontal dopamine and found a circuit mechanism for dopamine effects since delay discounting varied with tolcapone-induced changes in the left ventral putamen and the frontostriatal connectivity (Kayser et al, 2012). Drinking may thus escalate when decision-making processes in dopamine-innervated frontostriatal circuits are characterized by low executive control or high alcohol valuation (Camchong et al, 2014;Goschke, 2014;Sebold et al, 2022;Zucker, 2015). Chronic alcohol use reinforces this imbalance, thereby facilitating value-based impulsive and stimulus-driven habitual decisions that characterize dependent drinking (Camchong et al, 2014;Goschke, 2014;Sebold et al, 2022;Zucker, 2015).…”
Section: Neurobiology Of Decision-making and Related Drinkingmentioning
confidence: 99%